CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

If the coefficient of pth term in the expansion of (1+x)n is p and the coefficient of (p+1)th term is q then n =


A
p + q + 1
loader
B
p + q – 1
loader
C
p – q – 1
loader
D
p – q – 1
loader

Solution

The correct option is B p + q – 1
Coefficient of pth term = nCP1
Given nCP1=p(1),nCP=q(2)
(1)(2)P(nCP)=Q(nCP1)1(np)!p!=q1(n(p1)!(p1)pp=qn(p1)qnp+1
n = p + q – 1

Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
People also searched for
View More



footer-image